Forrest : The Confederacy's Relentless Warrior - Browning, Robert M., 1955- (Book collections on Project MUSE., 2004)
"Revered by some, loathed by others, Nathan Bedford Forrest has long been considered one of the greatest soldiers of the American Civil War. Responsible for his family at a young age, he quickly developed traits - self-reliance, decisiveness, and assertiveness - that would later make him famous. In business, the uneducated Forrest quickly made a fortune in various endeavors, including the slave trade. When the Civil War began, Forrest became an adept recruiter and leader, despite his lack of training in military science. His cavalrymen became famous for the forced marches, deception, and audacious battlefield maneuvers they used to defeat forces that often outnumbered them. In 1864, Forrest gained notoriety for his participation in the battle for Fort Pillow, Tennessee. In a controversy that persists today, the high casualty rate among African-American troops who surrendered there led to charges that Forrest's men had perpetrated a racially motivated massacre. After the war, Forrest became the first Grand Wizard of the Ku Klux Klan while promoting reconciliation between North and South amid the chaos of Reconstruction."--Jacket